The Implementation of the Merdeka Curriculum in the Penggerak School at SD Negeri Jawisari, Limbangan District, Kendal Regency - Sulistyono, Eko; Nurkolis, Nurkolis; Yuliejantiningsih, Yovitha (Jayapangus Press, 2025)
This study aims to examine the implementation of the Merdeka Curriculum at SD Negeri Jawisari, Limbangan District, Kendal Regency, which is one of the Penggerak Schools. This research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The findings indicate that the implementation of the Merdeka Curriculum at SD Negeri Jawisari is carried out through four main stages: planning, organizing, mobilizing, and supervising. The thorough planning involves all teachers in the preparation of administration, academic supervision, budget management, and periodic evaluations. The organization of implementation includes the determination of human resources, organizational development, assignment, and delegation of authority adjusted to the teachers' competencies. The mobilization of implementation is carried out through guidance and motivation from the principal to ensure optimal understanding and execution of the curriculum. Supervision is done by setting assessment instruments, periodic evaluations, and follow-ups involving all relevant parties. The main challenges faced include limited resources and a lack of teacher training. In conclusion, the success of the Merdeka Curriculum implementation highly depends on the effective role of the principal, active involvement of teachers, and support from parents and the community.